Partnership Formation Within Fiqh Muamalah of Toleration: Religious Residential Segregation in Muslim Minority Communities in France - Wildani Hefni; M. Khusna Amal; Qurrotul Uyun; Umar Chamdan (IAIN Manado, 2026)
This study examines how Muslim minorities in Paris, France, negotiate religious identity and civic belonging through partnership formation, drawing on fiqh al-aqalliyyat as a normative and adaptive legal framework. This study aims to identify how the Muslim minority shaped partnership formation through the principles of fiqh of muamalah in a complex context, within the constraints of French laicite and its strategy to secure religious practice and social participation. Based on qualitative in-depth interviews and drawing on secondary ethnographic research and textual examination of Islamic legal discourse, the study demonstrates that the Muslim minority in France negotiates a hybrid identity that reconciles Islamic ethical commitments with local communities within fiqh al-aqalliyyat. It’s driven by the challenges of being a minority in partnership formation, thus becoming both a survival strategy and a site of theological reinterpretation. This article argues that partnership formation operates as both an outcome of Islamic legal adaptation and a mechanism of identity negotiation, producing hybrid forms of Muslim citizenship that remain structurally constrained by securitization and socio-spatial marginalization. The partnership is embodied in the principle of maslahah, which is the most frequently invoked interpretive tool in minority jurisprudence. In line with this, this article contributes to global Muslim minority legal studies by showing how fiqh muamalah and fiqh al-aqalliyyat operate not only as normative doctrines but also as social mechanisms for negotiating partnership, dignity, and civic belonging in secular urban contexts.